Being Sundanese and Javanese Cultural Persons and Church Members - Tedjoworo, Hadrianus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2011)
For the Christians in Java, being cultural persons has been taken for granted in their daily life, but being church members is something that they are learning and realising in their participation in the church community. This distinction emerges when the faithful are committing themselves to the church along their journey through the sociocultural reality. In the ‘new’ community, which in the context of this article is the church, they see their being cultural persons in a different way and reimagine their identity in the daily experiences and the encounters with others. This article is an effort to listen to the believers’ imagination by considering their sociocultural images in imagining the church from within their local perspectives. Doing ecclesiology in this way is a journey to accompany and to listen to the local believers in search of their own ‘church’. The author puts the survey among the Catholics in two parishes in West and Central Java and the analysis of its results within the context of doing contextual theology of the church by qualitatively and intuitively exploring the local believers’ cultural images. Key Words:*Images, *Cultural images, *Church images, *Imagination, *Imagerial preference, *Participation, *Contextual and meaningful images, *Culturally embedded images Ecclesiology.